PENGADAAN TEMPAT SAMPAH PERCONTOHAN GUNA MEMBANGUN LINGKUNGAN SEHAT DI DESA PARPAREAN IV - Risda Hartati Sitorus; Reinhard Pardosi; Rionaldy Steven; Martuani Teresia; Tondi Paulus; Parsaoran Silalahi (Merwinspy Publisher, 2025)
The Student Service Practice Lecture (KPPM) activity aims to increase student empathy and concern for others. Each service group team is required to carry out a work program that benefits the village. Making trash cans is one of the work programs carried out by KPPM students. The purpose of this work program activity is to increase the awareness of the Parparean IV village community of the importance of protecting the environment and provide education to the village community not to litter and know the negative effects and dangers of waste on health, through the making of pilot bamboo bins and waste decomposition educational media boards. In addition, the purpose of this activity is to optimize public awareness to dispose of waste in the bins provided, and it is hoped that the community can also take advantage of existing natural resources to make their bins. The method of activities carried out consists of 3 stages, namely the planning stage in the form of licensing, the implementation stage in the form of making bins and educational media boards, and the final stage in the form of distributing bins. After the pilot bins were completed, the service team conducted limited socialization in several residents' homes, without holding formal events or large meetings. This socialization was carried out informally while interacting with residents, to convey information about the importance of cleanliness and waste management.